Psychological and Social Factors in Rheumatic Diseases - Sá, Maria do Céu; Oliveira, Abílio (Richtmann Publishing, 2012)
Rheumatic diseases are major causes of different degrees of pain, disability and deformity. They have strong impact inpatient’s lives, especially in psychological and social dimensions, as a result of their healthcare needs. The present study has aqualitative nature and is based on the evaluation of the impact of changes related to the progression of rheumatic diseases and on howthe disease affects patients, namely at psychological, professional and social level. We conducted a focus-group to understand howillness could limit the daily life of these adult patients, women and men, with rheumatic diseases. Along the analysis and discussion ofthe results, we found out that the patients with rheumatic diseases have a health condition extremely complex, particularly in apsychological and emotional dimension. They have suffered severe changes, associated to emotional disturbances, related withdemotivation, anxiety, nervousness, and physical limitations of multiple sorts, which lead to frustration or dissatisfaction. The rheumaticdiseases can strongly affect the profession and social activity of the patients, but the family and friends support was proven to have apositive impact in the individuals, softening some negative effects of the illness. Our study emphasizes that it is recommended that nursepractitioners participate in the evaluation of these patients, in order to provide the adequate healthcare that they require, and aiming topromote their wellbeing.